Comments on "Lyapunov and external stability of Caputo fractional order switching systems". (May 2021) - Hu, Jianbing
Abstract: The stability of Caputo fractional order switching systems is studied in the article by Wu C. etc (Wu and Liu (2019)). The authors claim that the lower bound of the Caputo fractional order derivative needs to be updated at each switching instant. However, the lower bound is relevant to the initial condition and reflects the historical information of a fractional system. No historical information can be changed by subsequent control input as all physical systems are causal systems. The model in Wu and Liu (2019) is physically unattainable and the theoretical achievements cannot be applied in engineering.